Azithromycin targets the CD27 pathway to modulate CD27hi T-lymphocyte expansion and type-1 effector phenotype - Ansari, Abdul Wahid; Jayakumar, Manju Nidagodu; Ahmad, Fareed; Venkatachalam, Thenmozhi; Salameh, Laila; Unnikannan, Hema; Raheed, Thesni; Mohammed, Abdul Khader; Mahboub, Bassam; Al-Ramadi, Basel K.; Hamid, Qutayba; Steinhoff, Martin; et al. (Frontiers in Immunology, 2024)
Macrolide antibiotic azithromycin is widely used in clinical practice to treat respiratory tract infections and inflammatory diseases. However, its mechanism of action is not fully understood.Given the involvement of CD27 pathway in the pathophysiology of various T-lymphocyte mediated inflammatory, autoimmune, and lymphoproliferative diseases, we examined the impact of AZM on CD27 regulation and potential consequences on CD4+ and CD8+ T cell phenotypes.Using cellular immunology approaches on healthy donors' peripheral blood mononuclear cells we demonstrate AZM-mediated downregulation of surface CD27 expression as well as its extracellular release as soluble CD27. Notably, AZM exposed CD27high (hi) cells were defective in their ability to expand compared to CD27intermediate (Int) and CD27low (lo) subsets. The defective CD27hi subset expansion was found to be associated with impaired cell proliferation and cell division. At molecular level, CD27hi subset exhibited lower mTOR activity than other subsets.Functionally, AZM treatment resulted in marked depletion of helper CD4+ (Th1) and cytotoxic CD8+ T-lymphocyte (Tc1) associated CXCR3+CD27hi effector cells, and inhibition of inflammatory cytokine IFN-γ production. These findings provide mechanistic insights on immunomodulatory features of AZM on T-lymphocyte by altering CD27 pathway. From clinical perspective this study also sheds light on potential clinical benefits observed in patients on prophylactic AZM regimens against various respiratory diseases and opens avenues for future adjunct therapy against Th1 and Tc1 dominated inflammatory and autoimmune diseases.